Internet addiction, social phobia, substance abuse, and depression in the university setting: a cross-sectional study in the southern region of Morocco - Ramdani, Fatima Zahra; Lahlou, Laila; Merzouki, Mohamed; Doufik, Jalal; El Oumary, Omar; Akebour, Khadija; Hamri, Saliha; Mouhadi, Khalid; Boujraf, Said; Rahioui, Hassan; Rammouz, Ismail (Frontiers in Psychology, 2024)
Aim Internet addiction is a mental health issue that can have detrimental effects on an individual’s life. This study aims to estimate the prevalence of Internet Addiction and identify the risk factors associated with this behavioral addiction. Methods This cross-sectional study was conducted in 6 universities in southern Morocco, involving 1,690 students who completed a self-administered questionnaire. The questionnaire collected socio-demographic data, and information on substance use, and included validated tools to assess Internet addiction (Young’s IADQ), depressive symptoms (Patient Health Questionnaire. PHQ-9), and social phobia (Mini Neuropsychiatric International Interview. M.I.N.I). Results The findings of our study indicate that the prevalence of Internet addiction was 30.60% (95% CI), depressive symptoms were present in 44.10% of participants, and the prevalence of social Phobia was 30.20%. A significant correlation was identified between early initiation of tobacco and Internet addiction (p = 0.05). The multivariate regression model revealed a possible association between cocaine use and Internet Addiction (OR = 5.67, IC 95%: 0.45 to 10.80) (p = 0.03), as well as a significant association between social phobia and a higher internet addiction score (OR = 3.45, IC 95%: 1.70–5.02) (p < 0.001). However, depressive symptoms were not significantly associated with internet addiction (p = 0.38). Conclusion These results highlight the urgent need to address internet addiction in the coming years. Implementing Multidisciplinary prevention strategies, early diagnosis, and follow-up measures are essential to mitigate the physical, psychosocial, and academic impacts of this addiction on students.